The prevalence and sectoral dynamics of earnings management: Evidence from the FBM KLCI - Timedjeghdine, Ghada; Eddine, Zeroual Sif (International journal of economic perspectives, 2025)
This study investigates the prevalence of earnings management among non-financial firms listed on the FTSE Bursa Malaysia KLCI (FBM KLCI) over the period from 2018 to 2022. Using discretionary accruals (DA) estimated through the Modified Jones Model, the research reveals a consistent trend of income-decreasing earnings management across the study period, with average DA values ranging between -0.00294 and -0.0034. Sectoral analysis shows significant variation in earnings management practices, with the technology sector demonstrating higher average DA values indicative of more aggressive financial reporting, while the construction sector displayed the most conservative behavior. The persistence of negative DA values, particularly during 2019–2021, coincides with the economic turbulence brought on by the COVID-19 pandemic, suggesting that firms engaged in income-decreasing strategies to smooth earnings, build financial resilience, and mitigate regulatory or stakeholder pressures. The significance of this study lies in its contribution to understanding how sector-specific characteristics and broader economic shocks influence financial reporting behavior in emerging markets. By providing empirical evidence from the Malaysian context, this research offers valuable insights for investors, regulators, and policymakers seeking to enhance corporate transparency and strengthen financial reporting standards.